Changes in crop mix and the effects on agricultural carbon emissions in China - Fei Meng; Hang Chen; Yongzhong Tan; Wenying Xiong (International Journal of Agricultural Sustainability)
Changes in crop mix significantly affect the carbon emissions from cropping systems, thus underscoring their importance in achieving sustainable agriculture development. This article aims to offer new insights into the relationship between crop mix changes and carbon emissions from cropping systems. Based on provincial statistical data on crop production, this study analyzed the spatiotemporal dynamics of crop mix and the subsequent effect on the carbon emissions from cropping systems in China from 2005 to 2020. The crop-mix type identification rules, emission-factor approach, and grey incidence analysis were applied. The results showed clear changes in crop mix and obvious transitions from grain crops to cash crops in southern provinces. Among crops, the abundance of maize, vegetables, and melons increased remarkably. Besides, the carbon emission intensity (CI) from cropping systems generally showed an upward trend in most provinces, with a spatial pattern of gradual decrease from southeast to northwest. The changes in CI were most closely correlated with rice, maize, vegetables, and melon, with coefficients of 0.808, 0.773, 0.814, and 0.792, respectively. Additionally, the growth of maize and vegetables ratios played a significant role in the CI increases in most provinces. To optimize crop cultivation and mitigate carbon emissions, possible strategies including rational crop production layout, land transfer, and clean production technologies were proposed.